The functional role of methylated short tandem repeats in early mouse development - Deakin, Greg (Cranfield University, 2011)
Short tandem repeats, or microsatellites are ubiquitous throughout all genomes that have been explored. In common with other sequences, the DNA in microsatellites has DNA marks in the form of chromatin methylation. Regulation of DNA methylation and changes in their pattern is critical for the establishment of unique cell states throughout development in mammals. DNA methylation is extensively reprogrammed during the early phases of mammalian development to establish unique developmental patterning. Whether microsatellites are also reprogrammed with developmental patterns is unknown. In this thesis, we assessed the characteristics of di- and trinucleotide microsatellites in the NCBIM37 Mus musculus assembly and observed a marked difference in quantity and length of microsatellites of differing motif, not explained by any known mechanism. Secondly we assessed the quantities of di-, tri- and tetranucleotide microsatellites in experimentally determined methylomes of Mus musculus at various stages in development. Our results indicate that at least one tetranucleotide microsatellite motif and more tentatively a second trinucleotide microsatellite follow a pattern of methylation consistent with reprogramming. Finally we show that the genes containing these specific microsatellites in the NCBIM37 genome have strong links to known developmental processes.
Keywords: microsatellites; DNA marks; DNA methylation; NCBIM37 genome; mammalian development